A Unique Case of Spontaneous Secondary Pneumothorax (SSP) Occurring during an Acute Exacerbation of Chronic Obstructive Pulmonary Disease (COPD). (June 2014) - Low, Lian Leng; Vasanwala, Farhad Fakhrudin
Spontaneous secondary pneumothorax (SSP) is a known complication and can occur during an acute exacerbation of chronic obstructive pulmonary disease (COPD) to confuse an unsuspecting physician. These patients have limited cardiopulmonary reserve, so can deteriorate quickly and require urgent management. We describe a unique case of SSP that occurred during an acute exacerbation of COPD, to remind physicians of this possibility and to re-examine their patients who are not improving as expected with nebulisation therapy.